Clinical Observation of the Correlation Between Overactive Bladder and Atopic Constitution in Children - Zheng, Yue; Zhang, Zhou; Hou, Ling; Wang, Xiuli; Jiang, Kailei; Zhang, Shucheng; Du, Yue (Frontiers in Pediatrics, 2021)
Objective: The present study aimed to analyze the risk factors correlated with overactive bladder (OAB), observe the effects of desloratadine in the treatment of OAB, and explore the correlation between OAB and atopic constitution in children. Methods: Correlation and binary logistic regression analysis of the medical data from 459 children clinically diagnosed with OAB from June 2019 to June 2020 were conducted. The data included a history of urticaria, eczema, itchy skin, and allergic rhinitis or allergic cough. The OABSS scores before and after treatment with desloratadine were compared to evaluate the effectiveness of desloratadine for OAB. Results: The risk factors for OAB in children included eczema, allergic rhinitis or allergic cough, itchy skin, and the levels of total blood IgE. Desloratadine was 96.5% effective in treating cases with risk factors including eczema, allergic rhinitis or allergic cough, and itchy skin. There existed statistical significance in the difference in OABSS scores before and after the treatment of desloratadine (P < 0.05). Conclusion: OAB in children was correlated with atopic manifestations such as eczema, itchy skin, allergic rhinitis, or allergic cough. Desloratadine was safe and effective in the treatment of OAB in children with atopic manifestations.